Mastering soft skills as the key to professional success for future specialists in agricultural business - Kramarenko, Tetiana; Крамаренко, Тетяна Володимирівна (Дніпровський державний аграрно-економічний університет, 2024)
In the ever-evolving landscape of agricultural business, the role of soft skills in the success of future specialists is becoming increasingly vital. This article explores the significance of soft skills in the context of agricultural business and emphasizes their importance alongside technical competencies. Through a review of existing literature and case studies, it is evident that soft skills such as communication, leadership, teamwork, and adaptability are crucial for navigating the complex challenges faced by professionals in this field. The article highlights the need for educational institutions and training programs to integrate soft skills development into their curricula to better prepare students for the demands of the agricultural business sector. Furthermore, it discusses the role of industry stakeholders in providing opportunities for practical skill development through internships, workshops, and mentoring programs. The purpose of the research is to offer a thorough examination of how soft skills function in the realm of learning foreign languages, to compare and contrast soft skills with hard skills, and to explore the benefits of incorporating these skills into the teaching practices of educators. The research is methodologically grounded on principles of scientific rigor, systematic approach, and objectivity. Various scientific methods such as analysis, synthesis, comparison, systematization, and generalization were employed in the paper’s development. The material is organized thematically, and a comprehensive exploration of the topic was achieved through the use of comparative, typological, and functional methods. Comparative analysis of the concepts “hard skills” and “soft skills” has been given in the article, emphasizing that hard skills are specific, teachable abilities or knowledge sets that are easily quantifiable and measurable. These skills are typically acquired through formal education, training programs, or on-the-job experience. Hard skills are often job-specific and can be defined and evaluated against specific criteria. Examples of hard skills include technical skills such as programming, data analysis, accounting, and proficiency in using specific tools or software. Unlike soft skills, which are more about how a person interacts with others and their environment, hard skills are more about what a person can do in a specific role or job. It has also been mentioned that soft skills refer to a cluster of personal qualities, habits, attitudes, and social graces that define one’s relationships, communication, and interactions with others. These skills are typically difficult to measure and quantify, as they are not specific to any particular job or task, but are crucial for effective functioning in the workplace. Examples of soft skills include communication skills, teamwork, problem-solving abilities, adaptability, creativity, and emotional intelligence. Unlike hard skills, which are technical and job-specific, soft skills are transferable across different jobs and industries. 245 Overall, the findings suggest that mastering soft skills is essential for future specialists in agricultural business to thrive in their careers, foster innovation, and contribute effectively to the sustainable development of the agricultural sector. У аграрному бізнесі, який постійно розвивається, роль soft skills у успіх майбутніх спеціалістів стає все більш важливим. У цій статті досліджується значення soft skills в контексті аграрного бізнесу та підкреслює їх важливість поряд технічні компетенції. Завдяки огляду існуючої літератури та тематичних досліджень стає очевидним, що «м’які навички», такі як спілкування, лідерство, командна робота та здатність до адаптації, мають вирішальне значення для орієнтуватися в складних викликах, з якими стикаються професіонали в цій галузі. У статті висвітлюється необхідність інтеграції навчальних закладів та навчальних програм розвитку м’яких навичок у своїх навчальних програмах, щоб краще підготувати студентів до вимог сектор аграрного бізнесу. Крім того, обговорюється роль зацікавлених сторін у галузі надання можливостей для розвитку практичних навичок через стажування, семінари та менторські програми. Мета дослідження — запропонувати ретельний аналіз того, як функціонують навички м’якого спілкування сферу вивчення іноземних мов, щоб порівняти та порівняти м’які навички з жорсткими навичками та вивчити переваги впровадження цих навичок у педагогічну практику педагогів. Дослідження методологічно обґрунтоване на принципах наукової строгості, системності підхід, об'єктивність. Різні наукові методи, такі як аналіз, синтез, порівняння, систематизація та узагальнення. Матеріал є організовано тематично, а завдяки використанню досягнуто комплексного дослідження теми порівняльного, типологічного та функціонального методів. Порівняльний аналіз понять «хард навички» та «м’які навички» наведено в ст стаття, в якій наголошується, що жорсткі навички – це специфічні здібності, яким можна навчити, або набори знань, які є легко піддається кількісній оцінці та вимірюванню. Ці навички, як правило, набуваються через формальну освіту, навчальні програми або досвід роботи. Важкі навички часто є специфічними для роботи та можуть бути визначені і оцінюється за певними критеріями. Приклади складних навичок включають такі технічні навички, як програмування, аналіз даних, бухгалтерський облік і навички використання спеціальних інструментів або програмного забезпечення. На відміну від м’які навички, які більше стосуються того, як людина взаємодіє з іншими та своїм оточенням, важкі навички більше стосуються того, що людина може робити на певній посаді чи роботі. Також було зазначено, що м’які навички стосуються групи особистих якостей, звичок, ставлень і соціальних переваг, які визначають стосунки, спілкування та взаємодію з іншими. Ці навички зазвичай складні для вимірювання та кількісної оцінки, оскільки вони не стосуються конкретної роботи чи завдання, але є вирішальними для ефективне функціонування на робочому місці. Приклади м’яких навичок включають комунікативні навички, командна робота, здатність вирішувати проблеми, здатність до адаптації, креативність та емоційний інтелект. На відміну від жорсткі навички, які є технічними та специфічними для роботи, м’які навички можна переносити на різні роботи і промисловості. Загалом отримані дані свідчать про те, що опанування навичок м’якого спілкування є важливим для майбутніх спеціалістів у галузі сільськогосподарського бізнесу, щоб процвітати в їхній кар’єрі, сприяти інноваціям і ефективно сприяти сталий розвиток аграрного сектору.
Оволодіння soft skills як запорука професійного успіху майбутніх фахівців аграрного бізнесу
Keywords: hard skills; жорсткі навички; soft skills; м’які навички; agricultural sector; аграрний сектор; foreign language; іноземна мова; interaction; взаємодія; cultural competence; культурна компетентність